2019
DOI: 10.1016/j.jtho.2019.08.1771
|View full text |Cite
|
Sign up to set email alerts
|

P2.12-26 The Impact of Anlotinib for Relapsed SCLC Patients with Brain Metastases: A Subgroup Analysis of ALTER 1202

Abstract: and multivariable survival outcomes were assessed. Result: In the cohort of 5877 patients, 2892 (49%) received chemoradiation, 1300 (22%) received surgery with radiation or chemotherapy, 639 (11%) received chemotherapy alone, 628 (11%) received surgery alone, and 418 (7%) received radiation alone. Amongst patients receiving surgery, 1277 (66%) received a lobectomy or pneumonectomy. Likelihood of receiving surgery in combination with radiation or chemotherapy was higher in later years of diagnosis (15% in 2006 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The median PFS was significantly improved with anlotinib treatment in patients with baseline brain metastases when compared to placebo, median 3.8 versus 0.8 months, HR 0.15, P=0.0005. Similarly, the median OS was improved in patients with baseline brain metastases treated with anlotinib at median OS of 6.1 versus 2.6 months, HR 0.26, P=0.0061 (23). The similar PFS and OS hazard ratios in patients with baseline brain metastases when compared to the whole study population suggest that anlotinib may not have a CNS liability.…”
Section: Anlotinibmentioning
confidence: 84%
“…The median PFS was significantly improved with anlotinib treatment in patients with baseline brain metastases when compared to placebo, median 3.8 versus 0.8 months, HR 0.15, P=0.0005. Similarly, the median OS was improved in patients with baseline brain metastases treated with anlotinib at median OS of 6.1 versus 2.6 months, HR 0.26, P=0.0061 (23). The similar PFS and OS hazard ratios in patients with baseline brain metastases when compared to the whole study population suggest that anlotinib may not have a CNS liability.…”
Section: Anlotinibmentioning
confidence: 84%
“…In addition, angiogenesis and VEGF-VEGFR pathway play important roles in brain metastases, and the inhibition of VEGFR pathway can inhibit brain metastatic tumor growth ( 20 , 21 ). The subgroup analysis of ALTER 1202 study showed that third- or further-line anlotinib could bring significant survival benefit for patients with brain metastases at baseline compared with placebo ( 22 ). The combination of anlotinib with chemotherapy as first-line treatment for extensive-stage SCLC also showed promising clinical benefits (ORR: 80–89%; median PFS: 9.4–11.4 months) in previous phase II trials ( 23 , 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…There are prerequisites for a response to immunotherapy in the microenvironment of brain metastases. In addition, the efficacy of anlotinib in patients with brain metastases was proven by the ALTER 1202 trial subgroup analysis, which showed that the PFS of patients with brain metastases was prolonged by 3 months (3.8 vs. 0.8 months, HR 0.15), and OS was prolonged by 3.7 months (6.3 vs. 2.6 months, HR 0.23) (Cheng et al 2019 ). Therefore, for ES-SCLC patients with brain metastases, we recommend the use of anlotinib combined with ICIs as third-line treatment.…”
Section: Discussionmentioning
confidence: 99%